Learning Logs: Reflective Writing and Metacognition in Bioethics Courses - Lázaro, Marila; López-Echagüe, Camila; Gago, Fiorella (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2022)
Bioethics has become a framework for debate throughout the world and, as such, it is an indispensable subject in scientific fields, especially in those related to life sciences. Nowadays, there is a need for its teaching to include not only the identification of ethical problems but also deliberation and critical reflection on those problems in order, among other things, to participate in decision-making processes. The methodological strategies for this are crucial. This article provides an analytical description of the use of learning logs as a tool of reflection and metacognition in bioethics courses, based on the experience of professors at the Faculty of Sciences of the Universidad de la República (Uruguay). An analysis of students’ learning logs shows that this tool promotes complex reflective and self-reflective processes in which the development of skills such as abstraction, argumentation and problematization is manifested in an integrated way.